THE APPLICATION OF ICE BREAKING ACTIVITIES IN ENGLISH TEACHING FOR JUNIOR HIGH SCHOOL STUDENTS IN MTSN 11 AGAM - Oktavia Elya Zahra; Veni Roza; Ahsanul Husna (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
The journal entitled "Ice Breaking activities in teaching English for Junior High School students" aims to describe the process of ice breaking activities and the suitability of these activities with the principles of ice breaking activities. This research was conducted at MTsN 11 Agam using a qualitative approach. The participants in this study were one of the English teachers at the junior high school. The results of the study describe the process of ice breaking activities and the suitability of these activities with the principles of ice breaking activities. ice breaking activities used are "Tongue-twister, English Game". ice breaking activities begin by dividing students into groups, revealing the name of the ice breaking that will be applied, explaining the steps that must be carried out in ice breaking activities, and starting ice breaking activities by determining one of the students from several groups to repeat the words that have been conveyed by the teacher. Researchers also found that, ice breaking activities are generally started using mentioning the name of the ice breaking, giving instructions on how the ice breaking is done, conducting simulations, and starting ice breaking activities within five to 20 minutes. Furthermore, the results of the study shared that the ice breaking process carried out was in accordance with the principles of ice breaking.